Endometriosis and Vesico-Sphincteral Disorders - Fadhlaoui, Anis; Gillon, Tessa; Lebbi, Issam; Bouquet de Jolinière, Jean; Feki, Anis (Frontiers in Surgery, 2015)
Objectives: The aim of this mini review is to determine the relationship between endometriosis and urinary tract symptoms and to investigate the consequences of surgical treatment of mild to severe endometriosis, especially deep lesions, on the vesico-sphincteral function (lower urinary tract function). Materials and Methods: We performed a literature review by searching the MEDLINE database for articles published between 2000 and 2014, limiting the searches to the words: urinary tract, vesico-sphincteral, dysfunction, endometriosis, symptoms and surgery. Results: The incidence of vesico-sphincteral symptoms in endometriosis varies from 3.4 up to 15.4%. The frequency of such symptoms seems to be under estimated because of a lack of specific questionnaire including urinary symptoms. Urodynamic evaluation could help to detect unsuspected abnormalities. It seems that endometriosis surgery (particularly deep infiltrating lesions) is a purveyor of de novo urinary dysfunction, with an incidence varying from 6.8 up to 17.5%. Nerve sparing Processes such as neuro-navigators or neuro-stimulators seem to be promising techniques to avoid postoperative urinary tract dysfunction. Conclusion: A precise anamnesis and the use of specific validated questionnaires (IPSS and BFLUTS) improve the screening of vesico-sphincteral symptoms in case of endometriosis. No recommendation can be found in the literature about the place of urodynamic evaluation. Most publications lack of proof and therefore do not allow making recommendations about optimal treatment of endometriotic lesions to avoid urinary tract disorders.